ALIGNING CRYPTOCURRENCIES WITH ISLAMIC LAW: CHALLENGES, ETHICAL CONCERNS, AND REGULATORY SOLUTIONS - Rahmadani, Nova Mentari Putri; Fajar, Fajar (Universitas Islam Negeri Mataram, 2024)
Cryptocurrencies, underpinned by blockchain technology, present significant challenges to Islamic law due to their volatile nature, speculative tendencies, and lack of intrinsic value, which introduce elements of gharar (uncertainty) and maysir (gambling), both prohibited under Sharia. Additionally, cryptocurrencies' decentralized and pseudonymous nature has raised concerns about their potential misuse in money laundering and other criminal activities, further complicating their alignment with Islamic principles. The research emphasizes the need for a multi-faceted regulatory approach, incorporating Sharia advisory boards, asset-backed cryptocurrencies, and advanced RegTech solutions such as blockchain analytics and E-KYC protocols. By fostering collaboration among scholars, regulators, and financial experts, this study aims to bridge the gap between innovative financial technologies and Islamic law, promoting ethical growth and stability in the cryptocurrency market.